SPONGE (Callyspongia sp., Callyspongia basilana, and Haliclona sp.) CULTURE WITH DIFFERENT INITIAL EXPLANT SIZES - Rosmiati Rosmiati; Petrus Rani Pong-Masak; Emma Suryati; Muhammad Tjaronge (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2008)
Sponge global demand for industry and research needs far exceeds supply from the sea. Aquaculture is considered as the only viable method that can supply sufficient and sustainable quantities of sponges. Aquaculture method is also one of efforts to anticipate and avoid the over-harvesting of sponges in nature. However, culture methods need to be determined to provide the platform for commercial success. In this study sponges (Callyspongia sp., Callyspongia basilana, and Haliclona sp.) were successfully cultured by transplantation method using polyethylene net with the initial explant sizes of 1 cm, 3 cm, and 5 cm. The result showed that the sponge growth and survival rates were dependent on the species. Callyspongia sp. and Callyspongia basilana gave the highest growth and survival rates on the treatment 3 cm with the final explants length reached 12.20 ± 2.35 cm and 7.603 ± 0.93 cm and survival rates reached 98.33% and 36.67%. In contrast, Haliclona sp. had the highest growth (21.67 ± 0.25) and survival (95%) on treatment 5 cm. Nevertheless, among the three species, treatment using 3 cm and 5 cm of initial explant sizes did not show a significant difference. Therefore for the efficiency of explants use, the best initial explant length for culturing the three species of sponges is 3 cm.